Green Development Model of China's Small and Medium-sized Cities - Li, Xuefeng (Research Series on the Chinese Dream and China's Development Path,, 2018)
The book discusses how to establish a land-use system for small and medium-sized cities in order to promote low carbon economic development and to ensure sustainable development. It also presents the objectives and requirements of urban green development: The first objective is to establish a green city with ecological harmony. The second is the establishment of a people-oriented harmonious city, which is important for the green development of city. Drawing on past experience and combining this with the current situation in China's cities, it argues that the construction of people-oriented harmonious cities should be a priority. The third objective is to build multi-functional organic cities in which the urban function is relatively independent. Lastly, the fourth objective is to establish a city with unique charm, applying historical ways of thinking to today's world.